The methodology of multicriteria optimization in design of information systems of radio frequency identification - Филиппенко, Инна Викторовна (Eastern-European Journal of Enterprise Technologies, 2012)
The article reviews the specifics of the theory of multi-criteria optimization for the optimal solution for the information transmission systems design